Efficient synthesis of indole derivatives containing the tetrazole moeity utilizing an Ugi-azide post-transformation strategy - Nikbakht, Ali; Rominger, Frank (Synlett, 2018)
An efficient strategy has been developed for the synthesis of indole derivatives containing the tetrazole moiety using a AuCl3-catalyzed cyclization reaction. The precursors of the cycloadduct were easily prepared by an Ugi-azide 4-CR in methanol at room temperature. The merit of this protocol lies in its operational simplicity, readily available starting materials, high yields of product, and good functional group tolerance.